Insect—Symbiont Gene Expression in the Midgut Bacteriocytes of a Blood-Sucking Parasite. (18th February 2020) - Husnik, Filip; Hypsa, Vaclav; Darby, Alistair
Abstract: Animals interact with a diverse array of both beneficial and detrimental microorganisms. In insects, these symbioses in many cases allow feeding on nutritionally unbalanced diets. It is, however, still not clear how are obligate symbioses maintained at the cellular level for up to several hundred million years. Exact mechanisms driving host–symbiont interactions are only understood for a handful of model species and data on blood-feeding hosts with intracellular bacteria are particularly scarce. Here, we analyzed interactions between an obligately blood-sucking parasite of sheep, the louse fly Melophagus ovinus, and its obligate endosymbiont, Arsenophonus melophagi . We assembled a reference transcriptome for the insect host and used dual RNA-Seq with five biological replicates to compare expression in the midgut cells specialized for housing symbiotic bacteria (bacteriocytes) to the rest of the gut (foregut–hindgut). We found strong evidence for the importance of zinc in the system likely caused by symbionts using zinc-dependent proteases when acquiring amino acids, and for different immunity mechanisms controlling the symbionts than in closely related tsetse flies. Our results show that cellular and nutritional interactions between this blood-sucking insect and its symbionts are less intimate than what was previously found in most plant-sap sucking insects. This finding is likely interconnected to several features observed in symbionts in blood-sucking arthropods, particularly their midgut intracellular localization, intracytoplasmic presence, less severe genome reduction, and relatively recent associations caused by frequent evolutionary losses and replacements.